2017
DOI: 10.1021/acs.chemrev.7b00168
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Polymer Systems with Stimuli-Responsive Mechanical Properties

Abstract: Materials with switchable mechanical properties are widespread in living organisms and endow many species with traits that are essential for their survival. Many of the mechanically morphing materials systems found in nature are based on hierarchical structures, which are the basis for mechanical robustness and often also the key to responsive behavior. Many "operating principles" involve cascades of events that translate cues from the environment into changes of the overall structure and/or the connectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
242
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(244 citation statements)
references
References 287 publications
(461 reference statements)
2
242
0
Order By: Relevance
“…At the same time, the covalent crosslinks still maintain a good strength of materials. For example, the hydrogen bond, ionic bond, and metal‐coordination bond can be utilized as the sacrificial bonds for the investigation of dual‐crosslinking self‐healing materials …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the covalent crosslinks still maintain a good strength of materials. For example, the hydrogen bond, ionic bond, and metal‐coordination bond can be utilized as the sacrificial bonds for the investigation of dual‐crosslinking self‐healing materials …”
Section: Introductionmentioning
confidence: 99%
“…Muscle is capable of transforming chemical into mechanical energy through a complex process involving an electrical pulse from the brain that ultimately results in conformational changes in muscle fibers. Early examples of actuating materials were metal alloys, but over the past few decades numerous examples of polymeric actuating materials have been reported . Some early examples involved bilayer structures composed of a layer of conducting polymer such as polypyrrole on a non‐conducting layer .…”
Section: Selected Developments In Smart Polymersmentioning
confidence: 99%
“…Bending was induced by volume changes of the conducting polymer layer upon chemical or electrochemical doping. Many other types of polymers, such as PNIPAM, which exhibit swelling and deswelling behavior under different conditions can also be used in the bilayer design . Shape memory polymers have also been employed to achieve actuation .…”
Section: Selected Developments In Smart Polymersmentioning
confidence: 99%
“…[27] Materials science often requires smart materials (stimuliresponsive materials) [28] with unique properties, i.e., materials capable of changing their properties in a controlled way in response to external triggers. [32] Smart materials found immense applications, often interalia with the development of stimuli-responsive polymers, which has been highlighted in several reviews, [33,34] including those found in the area of soft robotics. For instance, manufacturing has been revolutionized by advances in 3D printing, [31] as well as entirely new methods for creating complex structures from unfolding or stretching of patterned 2D composites.…”
Section: Research Activities In Smlmentioning
confidence: 99%